Neutralizations of IL-17A and IL-21 regulate regulatory T cell/T-helper 17 imbalance via T-helper 17-associated signaling pathway in immune thrombocytopenia. (June 2015) - Hu, Yu; Wang, Xiuwen; Yu, Shuang; Hou, Yu; Ma, Daoxin; Hou, Ming
<x xml:space="preserve">Abstract</x> Objective: The imbalance of regulatory T cell/T-helper 17 (Treg/Th17) is critical for the pathogenesis of immune thrombocytopenia (ITP) and IL-17A and IL-21 are overexpressed in ITP. The effects and mechanisms of IL-17A and IL-21 in Treg/Th17 imbalance and ITP pathophysiology are not clarified. Methods: Peripheral blood mononuclear cells (PBMCs) and CD3+ T cells from ITP patients and healthy controls were treated with cytokines or antibodies to increase or neutralize IL-17A or IL-21 levels for 72 h. Treg/Th17 differentiation, apoptosis, proliferation and Th17 differentiation-associated transcriptional factors were analyzed. Results: Natural Treg/Th17 decreased in newly diagnosed ITP patients and recovered after remission. IL-17A or IL-21 increased Th17, decreased Tregs and downregulated Treg/Th17 in vitro. Conversely, neutralization of IL-17A or IL-21 decreased Th17, increased Tregs and up-regulated Treg/Th17. The reverse effects of IL-17A or IL-21 were mediated by Th17-associated transcriptional factors. IL-17A or IL-21 enhanced STAT-1, STAT-3, STAT-5 or RAR-related orphan receptor C (RORC), whereas anti-IL-17A or anti-IL-21 mAb downregulated STAT-1, STAT-5 or RORC transcripts in ITP PBMCs. Proliferation showed no significant difference. IL-21 inhibited apoptosis in ITP PBMCs. Conclusion: IL-17A and IL-21 induce Th17 and inhibit Tregs re-differentiation via Th17-associated signaling pathway in ITP patients in vitro. It highlights the potential value of IL-17A or IL-21 blockade as a novel therapeutic target for ITP.